Research on factors affecting participation intention in the circular economy of the youth in Da Nang City - Nguyễn Thị Thu Hà (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The circular economy helps reduce waste, optimize resources, and address environmental issues. This study evaluates the factors influencing the intention of Da Nang’s youth to participate in the circular economy. Data were collected from 352 individuals aged 18 - 40 using a convenience non-probability sampling method. PLS-SEM results indicate that personal economic benefits, attitudes toward the environment, and perceived behavioral control have significant positive impacts, while subjective norms and attitudes toward the decision do not affect their intention to participate in the circular economy. This implies that rather than being influenced by social pressure from important others; the youth are more impacted by their perception of practical benefits or supportive policies. The novelty of this research is its expansion of the theory of planned behavior and quantification of its impact, focusing on youth attitudes within a context of limited circular economy transition. Policy implications include integrating entrepreneurship support, innovation, and environmental awareness through education and communication, alongside investments in green infrastructure, to encourage youth participation in the circular economy, contributing to sustainable development.